A Study of Player Behavior And Social Influences to Purchase Intention Mobile Legends: Bang Bang In-Game Item - Subarkah, Windu Praditiyo; Santoso, Adi; Widhianingrum, Wahna (Journal of Entrepreneurship and Business, 2023)
Purpose: This quantitative study aims to analyze the interest in buying items and skins in the online game Mobile Legends in Indonesia, especially in East Java Province by looking at the psychological and social factors of game players. Player behavior is a psychological factor and social factors are social influence variables. Design/methodology/approach: The number of samples in this study was 310, the sampling method used purposive sampling. Respondents are active Mobile Legends game players who have participated in answering our research questionnaire. The data collection method uses online questionnaire distribution using Google Forms. Measurement of data using answers with a Likert scale of 1 to 10 with 1 point strongly disagree and 10 points strongly agree. Data were analyzed using the PLS-SEM method using Smart PLS 3.0 software. Findings: Player behavior includes achievement, challenge, escapism, and social interaction. Social influences consist of network externality and community involvement. The results of our research show that player behavior consists of achievement, challenge, escapism, and social influences such as network externality, and community involvement have a significant positive effect on Purchase Intention. Originality/value: This study explores the purchase intention of virtual item in the mobile legends game using the uses and gratifications theory (U&G). The application of U&G theory is seen from the behavior of the players. Social influences is also applied to see the influence from outside the players.